L'expression des valeurs dans une approche cognitive / Katarzyna Kwapisz-Osadnik. - Kwapisz-Osadnik, Katarzyna
Słowa kluczowe: value, axiology, cognitive linguistics, pre-conceptual scheme, conceptualisation, categorisation.